Timelike-Ruled and Developable Surfaces in Minkowski 3-Space E13 - Mofarreh, Fatemah (Frontiers in Physics, 2022)
In this paper, the timelike ruled and developable surfaces is constructed in Minkowski 3-space $\mathbb{E}_{1}^{3}$. By means of the E. Study's map, we show that dual forms of timelike ruled and developable surfaces can be obtained from coordinates and the first derivatives of the base curve at dual hyperbolic unit sphere as a new method to have this type of the surfaces. Also some examples were given.